Views towards the revolution history course of foreign students in Turkey - Zafer Tangülü; Beytullah Kaya (Institute of Advanced Engineering and Science, 2019)
Studying history in accordance with gaining the legitimacy of the official ideology and reaching the historical bases that will open the way for the national identity for all teaching stages starting from primary education to tertiary education has made the national history subjects and naturally the topics of the Principles of Atatürk and History of the Turkish Revolution course both important and valuable. Although the teaching of Principles of Atatürk and History of the Turkish Revolution course has a role in the realization of national goals in higher education, the universal messages the program contains clearly demonstrate that the course has also a universal role beside the national identity of it. The purpose of this study is to investigate the opinions of foreign students studying in Turkey towards Principles of Atatürk and History of the Turkish Revolution course. To this end, this research is a case study in the qualitative research design. 12 foreign students studying at Istanbul Sebahattin Zaim University participated the study. The participants of the study were selected by purposive sampling method among criterion sampling methods. The criterion to pick these students was that they were accepted on the condition that they did Principles of Atatürk and History of the Turkish Revolution course for at least one semester at university. 6 female and 6 male students participated the study. Semi-structured interview form with 5 questions was prepared in order to determine the opinions of students participating in the research and content analysis was utilized to analyze the data obtained from the research and discourse analysis methods were employed to present the data. The opinions of the participants were transcribed and similar responses were categorized under certain headings. Research findings show that students are of the opinion that the course is very necessary for them and that it helps them to get scholar knowledge on Turkish history and it also helps them to get accurate history knowledge.